The bulging effect and its relevance in high power laser beam welding. Issue 1 (November 2021) - Artinov, Antoni; Meng, Xiangmeng; Bakir, Nasim; Üstündağ, Ömer; Bachmann, Marcel; Gumenyuk, Andrey; Rethmeier, Michael
Abstract: The present work deals with the recently confirmed widening of the weld pool interface, known as a bulging effect, and its relevance in high power laser beam welding. A combined experimental and numerical approach is utilized to study the influence of the bulge on the hot cracking formation and the transport of alloying elements in the molten pool. A technique using a quartz glass, a direct-diode laser illumination, a high-speed camera, and an infrared camera is applied to visualize the weld pool geometry in the longitudinal section. The study examines the relevance of the bulging effect on both, partial and complete penetration, as well as for different sheet thicknesses ranging from 8 mm to 25 mm. The numerical analysis shows that the formation of a bulge region is highly dependent on the penetration depth and occurs more frequently during partial penetration above 6 mm and complete penetration above 8 mm penetration depth, respectively. The location of the bulge correlates strongly with the cracking location. The obtained experimental and numerical results reveal that the bulging effect increases the hot cracking susceptibility and limits the transfer of alloying elements from the top of the weld pool to the weld root.